Using Artificial Neural Network for Compensation of Semiconductor Thermistor Nonlinearity - Запорожець, О. В.; Штефан, Н. О. (2019 IEEE 8th International Conference on Advanced Optoelectronics and Lasers (CAOL), 2019)
A method for correcting the transformation function of a semiconductor thermistor using a nonlinearity compensator based on a three-layer perceptron is proposed. Using of computer simulation, the operability of the proposed method has been investigated, a comparative analysis has been carried out with polynomial compensators of nonlinearity.
Keywords: artificial neural network; perceptron; learning; compensation of nonlinearity